Auditors' perceptions of ethical behaviour at the small and medium audit firms / Rubiah Dalail and Asmah Abdul Aziz (Faculty of Business and Management ; UiTM Press, 2005)
This study attempts to understand factors influencing Malaysian auditors' ethical behavior, i.e., code of ethical conduct, people at the office or those at homes. The relationship between demographic traits of respondents and their perceptions on peers' unethical behavior are studied as the integrity of auditors will affect investors' perception of financial statements. Three hundred and ninety six questionnaires were distributed to Certified Public Accountants whose membership information indicated auditing specialties. The findings revealed that those with a major responsibility (i.e., Senior Audit Assistants) behave more ethically than those with a lesser duty-bound answerability (i.e., audit assistants). The survey revealed that audit assistants are repeatedly engaged in unethical behavior compared to senior managers who rarely engaged in such behavior. The code of conduct seems to play a vital role in moulding auditor's behavior in the workplace more than their peers and superiors. The spouse is reported to be a lesser influence on an auditor's ethical behaviour.